A circular economy model based on biomethane: What are the opportunities for the municipality of Rome and beyond?. (January 2021) - D'Adamo, Idiano; Falcone, Pasquale Marcello; Huisingh, Donald; Morone, Piergiuseppe
Abstract: This paper defines the roles of biomethane for a double-green transition, through the integration of an effective management of renewable energy and municipal waste. The authors perform an assessment of the potential transition of the municipality of Rome to a more sustainable transport system, based on the economic feasibility of production of biomethane as analysed with the Discounted Cash Flow methodology. The potential reduction of emissions is quantified considering biomethane, to be used as vehicle fuel instead of natural gas. The provision of subsidies is found to be an essential condition to support the development of the biomethane sector. The subsidies must be coordinated with other policies such as the construction and operation of new fuelling stations and the increase of vehicles fuelled by biomethane. Several economic indicators are used to support investors by defining the conditions in which the profitability and economic opportunities are quantified. The transformation of bio-wastes into clean energy, closes the loop and helps societies to make progress toward becoming circular economies, which can contribute to decarbonizing the transport sector. Results of these analyses are applicable in other municipalities, which are currently under-utilizing their organic wastes and by-products. Graphical abstract: Image 1 Highlights: Biomethane supports the development of CE models. Biomethane can contribute to a double green transition. . A total NPV varies from 4.6 million € to 63.3 million €. Do Nothing cost varies from 365 thousand € to 2872 thousand €. The decrease of GHG emissions ranges from 43 to 51 thousand ton CO2eq/year.